IMPLEMENTASI SISTEM RESI GUDANG (SRG) PADA KOMODITI JAGUNG: STUDI KASUS DI KABUPATEN TUBAN, PROVINSI JAWA TIMUR - Nurlia Listiani; Bagas Haryotejo (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2013)
Studi ini bertujuan mengkaji berbagai faktor yang mempengaruhi petani dalam memanfaatkan Sistem Resi Gudang dan menganalisis manfaat penerapan SRG di Kabupaten Tuban. Metode yang digunakan adalah model Decision Matrix Analysis dan Metode Value Tree Objective. Hasil analisis DMA menunjukkan bahwa faktor utama pemanfaatan SRG adalah ketersediaan sarana dan prasarana gudang. Manfaat terbesar yang diperoleh petani adalah keuntungan dari adanya selisih harga jual saat panen dengan paska panen. Namun demikian, belum semua petani bersedia menggunakan SRG. Oleh karena itu, penerapan SRG perlu (1) sosialisasi, edukasi, dan succes story agar dapat diikuti oleh para petani; (2) lembaga seperti koperasi untuk menampung hasil panen; (3) dryer khusus untuk komoditas jagung. This study aims to examine the various factors influencing the farmers in using the warehouse receipt system and to analyze the benefits and costs in applying SRG for corn in Tuban, East Java province. Decision Matrix Analysis model is used to analyze the main factors that control farmers to use the warehouse receipt system, while Value Tree Objective is used to analyze the benefit and cost from using the warehouse receipt system. Based on the DMA model, the main factor influencing the farmers in using the warehouse system is the availability of facilities and infrastructures that support the warehouse. The biggest benefit from using warehouse receipt system is a gain coming from the price difference between sale during harvest time and post harvest. However, there are still many farmers who are reluctant to use the system. In order to encourage farmers, the implementation of SRG needs (1) socialization, education, and presenting success story; (2) the establishment of an institution like cooperative to load the harvest; (3) provision of special drier for corn.